Treatment patterns and disease outcomes for pediatric patients with refractory or recurrent Hodgkin lymphoma treated with curative-intent salvage radiotherapy. (May 2019) - Tinkle, Christopher L.; Williams, Noelle L.; Wu, Huiyun; Wu, Jianrong; Kaste, Sue C.; Shulkin, Barry L.; Talleur, Aimee C.; Flerlage, Jamie E.; Hudson, Melissa M.; Metzger, Monika L.; Krasin, Matthew J.
Highlights: rrHL is responsive to salvage RT, with a low LF rate after moderate RT doses. Overall survival of rrHL is excellent, despite refractory disease. The response of rrHL to initial salvage therapy predicts subsequent LF. Progression after omission of upfront RT or transplantation at failure can be salvaged. Abstract: Background and purpose: The use of radiotherapy (RT) for pediatric patients with Hodgkin lymphoma (HL) experiencing disease progression or recurrence (15%) is controversial. We report treatment patterns and outcomes for pediatric patients with refractory/recurrent HL (rrHL) treated with curative-intent RT. Materials and methods: Forty-six patients with rrHL treated with salvage RT at our institution were identified. All received risk-adapted, response-based frontline therapy and were retrieved with cytoreductive regimens followed by RT to failure sites, with or without autologous hematopoietic cell transplantation (AHCT). Cumulative incidence (CIN) of local failure (LF) and survival were estimated after salvage RT and regression models determined predictors of LF after salvage RT. Results: RT was administered as part of frontline therapy in 70% of patients, omitted for early response assessment in 13%, or deferred for primary progression in 17%. AHCT was omitted in 20% of patients. Median initial and salvage dose/site were 25.5 Gy and 30.6 Gy, respectively. Eight patients experienced progression. Two died without progression (median follow-up from salvage RT = 3.8 years). The 5-year CIN of LF after salvage RT was 17.7% (95% confidence interval [CI], 8.2–30.2%). The 5-year freedom from subsequent treatment failure and overall survival (OS) was 80.1% (95% CI, 69.2–92.6%) and 88.5% (95% CI, 79.5–98.6%), respectively. Inadequate response to salvage systemic therapy ( p  = 0.048) and male sex ( p  = 0.049) were significantly associated with LF after salvage RT. Conclusion: rrHL is responsive to salvage RT, with low LF rates after moderate doses. OS is excellent, despite refractory disease. Initial salvage therapy response predicts subsequent LF.